PENGARUH PEMBERIAN PUPUK KANDANG KOTORAN SAPI DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescens L.) DI GREEN HOUSE FMIPA UPG 1945 NTT - Adela Christiani Missa; Nardi Matias Leo; Nur Aini Bunyani (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study aimed to determine the effect of cow manure application on the growth of cayenne pepper (Capsicum frutescens L.) and to identify the most effective dosage for optimal plant growth. The research was conducted at the Biology Greenhouse, Faculty of Mathematics and Natural Sciences, Universitas Persatuan Guru 1945 NTT, Kupang, from January to March 2026. An experimental method was employed using a Completely Randomized Design (CRD) consisting of four treatments and five replications, resulting in 20 experimental units. The treatments were A0 (soil without cow manure), A1 (soil + cow manure at a ratio of 1 kg : 1 kg), A2 (soil + cow manure at a ratio of 1.5 kg : 0.5 kg), and A3 (soil + cow manure at a ratio of 0.5 kg : 1.5 kg). The observed parameters included plant height and number of leaves. Data were analyzed using Analysis of Variance (ANOVA) followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that the application of cow manure significantly affected the growth of cayenne pepper plants. Treatment A1 produced the best growth performance, with an average plant height of 18.18 cm and an average leaf number of 17.53 leaves. The increase in plant growth was attributed to the availability of essential macronutrients such as nitrogen, phosphorus, and potassium, which play important roles in tissue formation, photosynthetic activity, and vegetative development. In addition, cow manure improved the physical, chemical, and biological properties of the soil, thereby enhancing nutrient availability and uptake by plants. Based on the findings, it can be concluded that cow manure application positively influenced the growth of cayenne pepper plants, with treatment A1 providing the most effective dosage for optimal growth.